Role Of Ayurveda In Prevention Of Garbhini Madhumeha (Gestational Diabetes Mellitus) - Priyanka, V (International Research Journal of Ayurveda & Yoga, 2021)
Gestational diabetes mellitus is one of the common problem during pregnancy due to altered life style and diet pattern. Prevalence of GDM has been greatly increased since 10 yrs, in which 90% of diabetes in pregnant women is gestational and 10% is pre gestational. Healthy state of pregnancy could be possible by adopting Garbhadhana vidhi. Garbhini paricharya. Further samsodhana followed by rasayana, vajikarana as a part of Garbhadhana vidhi prevents possibilities of different ailments during pregnancy. Similarly, Garbhini paricharya that includes aahara, vihara, oushadha prescribed with monthly variations may also prevent several ailments during pregnancy. Any violations in the said regimen may lead to Atiyoga, Ayoga and Mithya yoga resulting in to diseases such as madhumeha particularly santarpana janya vikara and aavaranajanya madhumeha. In Madhu kosa vyakhya, it is explained that women with irregular menstruation are more prone to diabetes in their future pregnancy.Concept of Asta vidha aahara vishesha ayatana also plays a role in prevention of diabetes. Aahara vidhi also varies from sthula pramehi to krusha pramehi. viharas such as yoga and pranayama during pregnancy helps to reduce anxiety and endocrine measures. Finally, there is need to adopt for safer management of GDM through Ayurvedic principles.